(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The present paper is primarily an attempt tounderstand the patterns of religiousworship in the village Khera Khurd of north-west Delhi. It discusses the microlevel perspective of the issues with reference to the current beliefs andpractices that are a significant part of the sacred lives of the peasantcommunities. There are several ways to study religion among which texts oftenhave been given a fundamental place. Textual prescriptions and proscriptions,however, can have a marginal role in the world of folk worship. Therefore, inthis case, diverse forms of customs and traditions of the various communitieswhich coexist and which can be observed are studied from the perspective ofarchaeology. The aim of the work is to analyze ‘rural religion’ with specialreference to archaeological evidence from select the village in order tounderstand the interconnected aspects of the sacred geography of the area as awhole. The reason to choose the area to study these aspects is that the villageis in close proximity to the urban parts of the city where ‘Brahmanic religioustraditions’ hold prominence, however, it will be argued that though thereligious lives of the villages are not untouched by city culture, in thesacred universe of the peasant communities, local deities are moresignificance.